Expressões territoriais camponesas da comunidade Boa Esperança/Frutal (MG): os equilíbrios da unidade camponesa frente ao avanço do agronegócio canavieiro - Mendes, Heitor Nascimento (2018)
Faced with the expansion of sugarcane and sugarcane plantations in the Triângulo Mineiro, especially since the 2000s, we observed new territorial (re)organizations that incorporate elements to the social reproduction strategies of the peasants of this region, established from the relationship between the corporate logic of sugar-energy production and peasant agriculture. The Boa Esperança community, located in the City of Frutal (MG), has in its history a diversified peasant production, but the process of advance of the sugarcane front has been limiting and imposing a series of transformations and, consequently, adaptations in the productive and sociocultural scope of families. This movement was evident from the year 2006, with the installation of two plants of the sector in the township. In this sense, this dissertation aims to analyze these aspects from the notion of peasant equilibria proposed by Jan Douwe van der Ploeg, re-evaluating the conjuncture that made possible the new dynamics observed in the community, the characteristics of peasant organizations in the contemporary rural, and the strategies established from the conflict between the territory of the capital and the peasant, and thus we can draw prospects for rural development for the municipality of Frutal (MG), and advance in Ploeg theory, based on an empirical analysis of the equilibria. In spite of the subjection and the difficulties in maintaining themselves as "countrymen", the peasants reinvent themselves and seek in the impossibility of political confrontation with the mills, elements that preserve them, creating strategies binds the work, the bonds of solidarity, reciprocity, autonomy and resistance.